Analisis Model,Media dan Asesmen Dalam Pembelajaran IPAS Kelas V di SDN Kalianget Barat III - Kasumo Dwi Ayu Rindika Putri; Putra Dedy Dermawan; Sitti Nurhalizah; Firda Ayu Agustin (LPPM Sekolah Tinggi Ilmu Tarbiyah Muhammadiyah Bojonegoro, 2025)
This study aims to analyze the implementation of models, media, and assessments in Natural and Social Sciences (IPAS) learning in Grade V of SDN Kalianget Barat III. Elementary education plays a crucial role in shaping children's cognitive foundations, creativity, and character. This study used a descriptive qualitative method through observation and interviews with class teachers. The results showed that the dominant methods were lectures and experiments, chosen because they were considered effective and enjoyable for Grade V students who are in the complex concrete operational thinking phase. Teachers also implemented active models such as Problem-Based Learning (PBL) and Cooperative Learning to improve understanding and learning outcomes, as well as achieve the main goal of instilling student independence and collaboration. The media used included interactive media (video) and Chromebooks. However, there were significant obstacles in the form of limited infrastructure and low interest in student science literacy. The assessment used was formative with multiple-choice and descriptive techniques, but evaluation still tended to focus on the cognitive aspect, so that the affective and psychomotor aspects were not optimally measured. The study concluded that a more comprehensive integration of assessment techniques, such as portfolios or projects, was needed to support the achievement of balanced learning objectives in accordance with the main philosophy of the National Curriculum. Penelitian ini bertujuan menganalisis implementasi model, media, dan asesmen dalam pembelajaran Ilmu Pengetahuan Alam dan Sosial (IPAS) di Kelas V SDN Kalianget Barat III. Pendidikan dasar memiliki peran krusial dalam membentuk fondasi kognitif, kreativitas, dan karakter anak. Penelitian ini menggunakan metode kualitatif deskriptif melalui observasi dan wawancara dengan guru kelas. Hasilnya menunjukkan bahwa metode yang dominan adalah ceramah dan eksperimen , dipilih karena dianggap efektif dan menyenangkan bagi peserta didik kelas V yang berada pada fase berpikir operasional konkret yang kompleks. Guru juga menerapkan model aktif seperti Problem-Based Learning (PBL) dan Cooperative Learning untuk meningkatkan pemahaman dan hasil belajar, serta mencapai tujuan utama menanamkan kemandirian dan kolaborasi siswa. Media yang digunakan meliputi media interaktif (video) dan Chromebook. Meskipun demikian, terdapat hambatan signifikan berupa keterbatasan sarana prasarana dan rendahnya minat literasi sains siswa. Asesmen yang dipakai adalah formatif dengan teknik pilihan ganda dan uraian , namun evaluasi masih cenderung fokus pada aspek kognitif, sehingga aspek afektif dan psikomotor belum terukur optimal. Penelitian menyimpulkan bahwa diperlukan integrasi teknik penilaian yang lebih komprehensif, seperti portofolio atau proyek, untuk mendukung pencapaian tujuan pembelajaran yang seimbang sesuai filosofi utama Kurikulum Nasional.